NILAI PENDIDIKAN KARAKTER PADA TOKOH DATU SANGGUL DAN RELEVANSINYA PADA PEMBELAJARAN BAHASA INDONESIA KELAS VII - Siti Haryawati (STKIP Paris Barantai, 2018)
Basically literary works are a means that can be used to support education. With the education system as it is today, the values ​​that should be the equipment of Indonesian people in the context of facing the era of globalization with local wisdom have not really been implemented or ignored. Education through school introduces more students to outside cultures than knowing the culture of ancestral heritage. Introductions to local culture occur only by chance for certain individual or group businesses. Thus the next generation in this case students do not have time to re-read, interpret, and create meaning and utilize local culture in the development of national character. The people of South Kalimantan have many legends, especially religious legends and individuals. One of them is the Datu sanggul character. Datu sanggul is one of the great Sufi scholars and a khawwash. In addition to having a high level of knowledge, he is also known as a person who is famous. The method used in this study is a qualitative research method with a case study approach. according to Bogdan and Bikien in Sugiyono (2009), Case study is a detailed test of one setting or one subject person or a place for storing documents or a particular event. This research was conducted by exploring the life story of Datu Sanggul and reviewing books that wrote about the life story of Datu Sanggul. Judging from the history of Datu Sanggul, it can be concluded that the characters of Datu Sanggul characters contain exemplary character education values, namely religious, tolerance, discipline, independence, environmental care, social care, and communicative spirit that can be learned and followed. Based on content competencies and basic competencies in the 2013 class revision curriculum which contains material on (1) Fables / legends, (2) Characteristics of fable / legend stories (3) Steps to understand the contents of the story fable (4) Steps to retell the contents of fables / legends. So the legend of datu sanggul is very relevant to Indonesian language learning, especially for students in South Kalimantan to understand and study the local wisdom in their area. Keyword: Character Building, Figure, and Learning.